Optimized front TCO and metal grid electrode for module‐integrated perovskite–silicon tandem solar cells. (21st October 2021) - Messmer, Christoph; Tutsch, Leonard; Pingel, Sebastian; Erath, Denis; Schön, Jonas; Fell, Andreas; Goldschmidt, Jan Christoph; Goraya, Baljeet S.; Clement, Florian; Lorenz, Andreas; Nold, Sebastian; Bivour, Martin; et al.
Abstract: To unlock the full potential of perovskite–silicon tandem solar cells with >30% efficiency at presumably low cost, the transparent conductive oxides (TCOs) and metal grid at the front side need to be adapted compared to classical silicon heterojunction (SHJ) solar cells. By means of optical and electrical modelling, we consider the main aspects to optimize the front electrode for the tandem case, where in contrast to silicon single junction devices, there are (i) different optical properties including a lower refractive index of the perovskite absorber (ii) about half the current, thus quarter the resistive power losses for the same series resistance contribution (iii) lateral transport at the front needs to be provided solely by the front TCO layer and (iv) lower thermal stability of the perovskite, which affects TCO deposition conditions and results in a less efficient sintering of the silver screen printing pastes. This study concludes that compared to silicon heterojunction cells, the thickness of the front TCO should be reduced from 75 nm to around 20 nm, resulting in less parasitic absorption and a potential cost reduction of 1.46 €ct/cell for ITO. We investigate the impact of different front metallization including plating and silver screen printing and showcase that for multi‐wire interconnection concepts, the number of wires can be reduced from 18 wires to 9 or even less depending on the front metallization. Finally, we give an outlook on the silver consumption and levelized cost of electricity. Abstract : This work investigates module‐integrated perovskite–silicon tandem cells focusing on the front electrode, that is, the transparent conductive oxide (TCO) and the metal grid, by means of optoelectrical simulations. We elaborate on the optical and electrical properties of an adapted front TCO including thickness and sheet resistance variation, as well as the finger metallization including plating and silver screen‐printing and its implications on a multi‐wire interconnection concept. Finally, we give an outlook on the silver consumption and levelized cost of electricity.